2003
DOI: 10.1029/2003jd003566
|View full text |Cite
|
Sign up to set email alerts
|

Solubility properties of surfactants in atmospheric aerosol and cloud/fog water samples

Abstract: [1] Organic films on deliquesced aerosols and cloud droplets lower the surface tension of water and may inhibit the exchange of water vapor and gases between the gas and the liquid phase, with important implications for aerosol and cloud microphysics and heterogeneous chemistry. This study provides an estimate of the solubility properties of surfactants in aerosol and fog/cloud water samples on the basis of the dilatational rheological properties of the surface films. The variations of surface tension induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 23 publications
1
49
0
Order By: Relevance
“…σ 0 represent the surface tension of pure water at the temperature of measurements. Previous work Decesari et al, 2003) have shown that this equation well describes the surface tension changes in atmospheric water, and it was shown that the surface coverage of WSOC surfactants is mainly controlled by the bulk concentration of WSOC. In the case of micrometer sized droplets and strongly surface active compounds, Eq.…”
Section: Surface Tension Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…σ 0 represent the surface tension of pure water at the temperature of measurements. Previous work Decesari et al, 2003) have shown that this equation well describes the surface tension changes in atmospheric water, and it was shown that the surface coverage of WSOC surfactants is mainly controlled by the bulk concentration of WSOC. In the case of micrometer sized droplets and strongly surface active compounds, Eq.…”
Section: Surface Tension Measurementsmentioning
confidence: 99%
“…However, the partitioning effects demonstrated for sodium dodecyl sulfate (SDS) might be less important in the case of atmospheric surfactants (Rood and Williams, 2001;Sorjamaa et al, 2004;Facchini et al, 2001). Therefore, in this work we used the surface tension data as suggested by Decesari et al (2003), i.e. as being independent of the available surface area.…”
Section: Surface Tension Measurementsmentioning
confidence: 99%
“…The fact that η is determined with less precision was reported as well by Wüstneck et al [2] which found the confidential intervals (95% confidence level) of ε about 1-4%, whereas those for the η between 10 and 15%. Decesari et al [40] obtained an uncertainty on the ε determination of 10% for Π > 3 mN m −1 using the same instrument.…”
Section: Dependence Of η and ε On Oscillation Frequency And Amplitudementioning
confidence: 99%
“…Carbonaceous material (organic carbon, OC) can comprise up to 90% of aerosol mass (Andreae and Crutzen, 1997;Cachier et al, 1995;Yamasoe et al, 2000), 10-70% of which may be water-soluble (WSOC). Studies have shown that WSOC can influence aerosol hygroscopicity and surface tension (Decesari et al, 2003;Saxena and Hildemann, 1996;Shulman et al, 1996) and must be characterized to quantify the impact of these aerosols on cloud droplet formation. WSOC can be present in primary organic carbon but also formed during the oxidation of volatile organic carbon (VOC) to secondary organic aerosol (SOA) (Kanakidou et al, 2005;Robinson et al, 2007;Saxena and Hildemann, 1996).…”
Section: Introductionmentioning
confidence: 99%